2021
DOI: 10.1037/ocp0000313
|View full text |Cite
|
Sign up to set email alerts
|

The double-edged sword of manager caring behavior: Implications for employee wellbeing.

Abstract: While managers play a critical role in supporting employee wellbeing, prior research suggests that doing so can take a toll on managers themselves. However, we know little about the potential implications of this for employees. Drawing from the leadership-wellbeing literature and social psychological theories of guilt, we propose that manager caring behavior is associated with both positive (vitality) and negative (guilt) employee wellbeing. We find support for these relationships in Study 1 (N = 264) with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 96 publications
(148 reference statements)
1
9
0
1
Order By: Relevance
“…Intuitively, one could assume that managers’ caring behavior will improve follower well-being. In contrast to this intuitive idea, Boekhorst et al provide a much more nuanced view suggesting that manager caring behavior can also have negative consequences by making followers feel guilty.…”
Section: The Microscope: Leader and Follower Health/well-beingmentioning
confidence: 97%
See 2 more Smart Citations
“…Intuitively, one could assume that managers’ caring behavior will improve follower well-being. In contrast to this intuitive idea, Boekhorst et al provide a much more nuanced view suggesting that manager caring behavior can also have negative consequences by making followers feel guilty.…”
Section: The Microscope: Leader and Follower Health/well-beingmentioning
confidence: 97%
“…For instance, in industry sectors that have traditionally been characterized by long working hours and high job demands such as finance and banking, it may not be viewed as "acceptable" to show vulnerability and may be more difficult and risky to discuss mental health issues (as a leader and follower). Boekhorst et al (2021) found that in teams with a low caring climate, manager caring behavior can signal role overload to employees-so possibly unintended negative perceptions of difficulties in navigating their own workload.…”
Section: The Macroscope: Importance Of Context For Leadership and Wel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are views suggesting that over-use of care, such as "compassion fatigue" and "overloaded supervisor care, " may lead to negative outcomes (e.g., Duarte and Pinto-Gouveia, 2017). For example, Boekhorst et al (2021) showed that while managerial caring behavior was positively correlated with employee vitality in the workplace, its negative effect appears to be more pronounced when there were employee-rated manager overload and employee guilt.…”
Section: Introductionmentioning
confidence: 99%
“…Показано вплив різноманітних об'єктивних і суб'єктивних факторів на професійне благополуччя особистості. Професійне благополуччя пов'язане з організаційною культурою [16], а також із культурою управлінської взаємодії [17]. Фактором, що сильно підриває професійне здоров'я і почуття благополуччя були визнані плітки на робочому місці [18].…”
unclassified